Analysis of methods of synthesis of measuring signals for the control of the technical condition of radionavigation complexes of motion control means of water transport (Transport systems and technologies, 2019)
The article deals with the features of the contradiction that exists in the practice of controlling the technical condition of complex systems. It consists in the fact that the maintenance of the given reliability of the information on the technical condition of radionavigation complexes for controlling the movement of means of water transport requires an increase in the volume and accuracy of measurements in assessing their characteristics on the one hand, and on the other there is a lack of methods for automating the processes of synthesis of measuring signals and processing reviews for them for this.According to the results of the analysis of known methods of synthesis of measuring systems for monitoring the state of radionavigation complexes of motion control of water transport means, it is proposed to develop an optimal method for synthesizing measurement signals with the required spectrum and to experimentally verify the obtained theoretical results and to develop recommendations for their implementation for automated- the control of the technical state of the radionavigation complexes of the traffic control of means of water transport.The results of the work will solve the problem of ensuring the reliability of the control of the technical condition of the systems and complexes of navigation and control of the movement of water transport vehicles with optimal time characteristics in order to ensure the timeliness and operability of identifying possible failures during their operation and maintenance on the actual state.
Keywords: operation, radionavigation complexes, traffic management, means of water transport, methods, measuring signals, automation of control